Department of Statistics Malaysia Negeri Pahang Wisma Persekutuan Jalan Gambut 15000 Kuantan / Amirah Fasihah Mohammad Helmi - Mohammad Helmi, Amirah Fasihah (2012)
This research is intended to examine the most contributing motivational factor to the employee work performance of DOSM Negeri Pahang and also to determine whether there is significant difference in each selected demographic profile (Age, monthly salary, highest educational level and working experience in DOSM) on employee’s work performance and motivational factor. The knowledge about the factor that influences employee work performance is much needed to maintain or improve employee’s work performance. In this study, researcher use self-administered questionnaire to gather the data from permanent employees of DOSM Negeri Pahang as respondents. The questionnaire has been distributed about 80 set to employees. The dependent variable is employee’s work performance of DOSM Negeri Pahang and independent variables are organization culture(X1), Facilities and other services(X2), Colleague(X3), recognition(X4), work-itself(X5), career development(X6) and Family relationship(X7). There are 100 permanent employees which is available during the research is conducted. By using simple random sampling about 80 samples of employees of DOSM Negeri Pahang is taken. For analyzing the data researcher used software SPSS 18. Method of regression analysis and one-way ANOVA are used to test the all the objective. The findings of the study show that the most contributing factor is intrinsic motivation which are factor of work-itself and family relationship. The study also found that there is no significant difference in each demographic profile and performance. But, there is significant difference in age and monthly salary toward employees’ motivational factor of DOSM Negeri Pahang, while there is no significant difference in working experience in DOSM toward employee’s motivational factor